Upaya Menanamkan Literasi Lingkungan Siswa MDT Raudhatul Mubtadiin, Sumenep - Matlubah, Helliyatul; Herowati, Herowati; Novita Punggeti, Ratna (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service aims for conducting a waste-management training for students of Madrasah Diniyah Taklimiyah Raudhatul Mubtadiin in Bates Village as an effort of embedding environmental literacy at an early age. Methodology: The program was conducted as a face-to-face training for students of Madrasah Diniyah Taklimiyah Raudhatul Mubtadiin in Bates Village, Sumenep Regency, East Java which involved 22 students. This activity was carried out through three stages, including planning, implementation and evaluation stages. The implementation of training includes presentation about waste, its types and management and practice how to recycle non-organic waste. Results: The community service was attended by 22 MDT Raudhatul Mubtadiin students from Bates Village which consisted of 11 male and 11 female students. After the training session, students’ understanding and skills in terms of waste and how to manage organic and non-organic waste have improved. The results were shown by the majority of students’ correct responses toward questions asked in evaluation stage. Conclusions: The waste management training ran smoothly and it succeeded to improve students’ environmental literacy especially for understanding and skills components. Limitations: The materials given were limited to organic and non-organic waste and the practical stage of training was only about recycling plastic bottle excluding the training of how to make compost from organic waste due to time constraints. Contribution: This activity may contribute to embed and enhance students’ knowledge and skills regarding waste and its management. Moreover, this also can improve students’ awareness toward their environment.